Visceral adipose tissue alteration of PI3KR1 expression is associated with gestational diabetes but not promoter DNA methylation. (2nd January 2019) - Rancourt, Rebecca C.; Ott, Raffael; Schellong, Karen; Melchior, Kerstin; Ziska, Thomas; Henrich, Wolfgang; Plagemann, Andreas
ABSTRACT: Obesity and diabetes are at an epidemic rate, as well as growing incidences of gestational diabetes mellitus (GDM) which causes pregnancy risks, and harm in both maternal and child health. It remains unclear which molecular mechanisms are driving the functional differences between visceral and subcutaneous fat and how these types directly affect an individual's health outcome. Paired abdominal subcutaneous and omental visceral adipose tissue were collected from women with GDM (n = 20) and with normal glucose tolerance (NGT, n = 22) during planned caesarian section. Both groups had similar maternal age (average 32.5 years) and BMI at delivery (average 33.3 kg/m 2 ). Adipose tissue mRNA expression analyses of insulin signalling genes: PI3KCA, PI3KR1, IRS1 and IRS2 showed significantly decreased PI3KR1 expression (−23%) in visceral fat in GDM with no association to promoter DNA methylation. Reduced visceral fat PI3KR1 expression appears to be a pathogenic factor in GDM but not through altered promoter methylation.